1998
DOI: 10.1530/jrf.0.1120337
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of oxytocin in the intercavernous sinus of mares during luteolysis: temporal relationship with concentrations of 13,14-dihydro-15-keto-prostaglandin F2 

Abstract: The reproductive tracts of nine thoroughbred mares were examined by ultrasound to determine the day of ovulation (day 0). Mares were fitted with intercavernous sinus cannulae on the day before the start of sample collection of pituitary venous effluent rich in oxytocin. Intercavernous sinus blood samples were collected for at least 36 h at 5 min intervals beginning at noon on day 13 (n = 2), day 15 (n = 5) or day 16 (n = 2) after ovulation. Concentrations of oxytocin and 13,14-dihydro-15-keto prostaglandin F2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 0 publications
0
21
1
1
Order By: Relevance
“…Daily application of OT to mares at days 4, 5, 6, 7 and 8 of the oestrous cycle had no effect on PGFM concentrations and duration of dioestrus (Neely et al 1979), supporting the hypothesis of downregulated OTreceptors up to day 10 of the cycle. In contrast, Vanderwall et al (1998) could not find synchronous OT and PGFM patterns in blood samples, which were drawn from the cavernous sinus during luteolysis, although they support the positive feedback role of OT on PGF 2α as well.…”
Section: Oestrous Cyclecontrasting
confidence: 69%
“…Daily application of OT to mares at days 4, 5, 6, 7 and 8 of the oestrous cycle had no effect on PGFM concentrations and duration of dioestrus (Neely et al 1979), supporting the hypothesis of downregulated OTreceptors up to day 10 of the cycle. In contrast, Vanderwall et al (1998) could not find synchronous OT and PGFM patterns in blood samples, which were drawn from the cavernous sinus during luteolysis, although they support the positive feedback role of OT on PGF 2α as well.…”
Section: Oestrous Cyclecontrasting
confidence: 69%
“…Oxytocin is synthesized in the hypothalamus, stored in the posterior pituitary, and secreted in pulses [11,12]. The CL also synthesizes and secretes OT during the estrous cycle in domestic ruminants [13,14], but the CL apparently does not secrete OT in mares [15].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that when oxytocin treatment is initiated before day 10 postovulation, it prevents luteolysis by inhibiting the increase in endometrial oxytocin receptor concentration that would otherwise permit endogenous oxytocin-induced PGF2a secretion at the time of luteolysis; however, there was no difference in endometrial oxytocin-binding capacity between salinetreated control mares and oxytocin-treated mares in this study, which does not support that hypothesis. It is possible that oxytocin treatment prevents luteolysis through a different mechanism or that our experimental methods were not sensitive enough to detect a difference in oxytocin receptor concentrations between groups; for example, cervical manipulation induces an acute release of oxytocin from the posterior pituitary gland in nonpregnant mares [13], and because the endometrial tissue samples in this study were obtained transcervically, it is plausible that release of endogenous oxytocin could have led to the saturation of endometrial oxytocin receptors, which prevented us from detecting a difference between groups. Therefore, further work will be needed to determine the mechanism through which oxytocin treatment disrupts luteolysis, leading to prolonged CL function in mares.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous oxytocin secretion is involved in regulating prostaglandin F2a (PGF2a) secretion from the endometrium during spontaneous luteolysis in the mare [13,14], and although administration of exogenous oxytocin to mares around the time of luteolysis (i.e., days 11-15 postovulation) stimulates an acute onset of PGF2a secretion [15][16][17], when oxytocin is administered in the midluteal phase before the expected time of luteolysis (i.e., before day 10 postovulation), it does not induce PGF2a secretion and often disrupts spontaneous luteolysis causing prolonged CL function [16,18]. We previously reported the results of a "proof of principle" study [7] that showed IM administration of 60 U of oxytocin twice daily on days 7-14 postovulation was an efficacious method of disrupting luteolysis because it caused prolonged CL function through day 30 postovulation in all six treated mares, whereas all six saline-treated control mares underwent spontaneous luteolysis by day 16 postovulation.…”
Section: Introductionmentioning
confidence: 99%